Kenya - Karurumo village - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Ruth Marigu Njue is a female farmer and a widow from Kenya who works hard to sustain her family of ten. She faces several obstacles in the form of lack of rain and a warmer climate. To adapt she has started using seeds that grow faster, to avoid pests. She has also started planting trees to optimize water retainment.